Form-Bilding Factors of the Generational Novel (by the example of novels “Heavenly bodies” by T. Dückers and “In my brother’s shadow” by U. Timm) - Hrecheshnyuk, Olya (Pitannâ lìteraturoznavstva, 2020)
The article deals with the problem of the form-bilding factors of the generational novel by the example of the most popular novels of the modern German literature (“Heavenly bodies” by T. Dückers and “In my brother’s shadow” by U. Timm). At the beginning of 21th century the question about the nature of a generational novel, as a specific kind of the family novel, is the most discussed among the specialists in literature. The work is based on research of the important works of famous scientists (A. Assmann, A. Eichenberg, M. Neuschäfer and other). The research demonstrates, that the most significant poetical details of this genre variety apply to its composition. The results of the research show that all generational novels have special structural elements, which are its form-bilding factors (specific composition form, position of the narrator, characters and other). The paper is based on structurally-typological and comparative approaches, which help to reveal the specificity of the generational novel as a genre variety. Scientific novelty contains the try to describe the features of the poetics of the generational novel in the modern German literary process. Despite the actuality of such problem of the generational novel and the existing works this theme is analyzed only a little. That is the reason for research on this topic.